Growth performance and nutrition value of Spirulina sp. under different photoperiod - Tatag Budiardi; Nur Bambang Priyo Utomo; Asep Santosa (Jurnal Akuakultur Indonesia, 2010)
This study was conducted to analyze the production of freshwater Spirulina sp. cultured with photoperiod manipulation treatment. In this study, photoperiod manipulation treatment performed on cultured spirulina using fiber tanks (100 L). Spirulina was grown with different photoperiod (bright/T and dark/G) that are six hours per day (6T-18G), 12 hours per day (12T-12G), 18 hours per day (18T-6G), and 24 hours per day (24L-0G). The parameters were observed include dry biomass, population density (N), specific growth rate (SGR), doubling time (G), proximate analysis, and water quality. The results of this study showed that the optimum population density was achieved on day-3 days of cultured, and manipulation photoperiod showed no significant effect to the dry biomass harvest and population density, but significantly affect the specific growth rate and doubling time. Treatment of lighting 12, 18 and 24 hours per day to produce the maximum specific growth rate (0,345 to 0,366 per day) and a maximum doubling time (1,89 to 2,01 days) were not significantly different, whereas the old treatment six hours per day lighting showed the lowest maximum growth rate (0,323 per day) and highest doubling time (2,15 days). At treatment of lighting 12 hours per day, relatively higher protein content (39,73%) than others. In conclusion, the lighting 12 hours per day resulted in optimum production efficiency than other treatments.